2022
DOI: 10.1039/d2ra01897g
|View full text |Cite
|
Sign up to set email alerts
|

Emerging application of biochar as a renewable and superior filler in polymer composites

Abstract: Biochar is a low-cost carbon material with excellent thermal characteristics. Despite having remarkably similar properties to graphene and carbon nanotubes, it is rarely used as a polymer filler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 97 publications
(161 reference statements)
0
20
0
2
Order By: Relevance
“…Biochar has generally been exploited at the pre-industrial scale as soil amendment [ 8 ], though it has found many other applications ranging from environmental remediation [ 9 ], energy storage [ 10 ] and catalyst support [ 11 ]. Many research studies have highlighted that the addition of biochar particles results in polymer composites with improved flexural and tensile properties, enhanced impact strength and higher heat deflection temperature [ 7 , 12 , 13 , 14 , 15 ]. Additionally, it was demonstrated that biochar can bestow electrical conductivity, flame retardance and wear resistance both to thermoset and thermoplastic-based systems [ 16 , 17 , 18 , 19 , 20 ], demonstrating its potential to replace conventional and expensive carbonaceous fillers derived from fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…Biochar has generally been exploited at the pre-industrial scale as soil amendment [ 8 ], though it has found many other applications ranging from environmental remediation [ 9 ], energy storage [ 10 ] and catalyst support [ 11 ]. Many research studies have highlighted that the addition of biochar particles results in polymer composites with improved flexural and tensile properties, enhanced impact strength and higher heat deflection temperature [ 7 , 12 , 13 , 14 , 15 ]. Additionally, it was demonstrated that biochar can bestow electrical conductivity, flame retardance and wear resistance both to thermoset and thermoplastic-based systems [ 16 , 17 , 18 , 19 , 20 ], demonstrating its potential to replace conventional and expensive carbonaceous fillers derived from fossil fuels.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the higher the filler concentration, the lower the measured complex viscosity. This behaviour can be attributed to the poor chemical interaction at the polymer-filler interface and the lubricant effect offered by the partial degradation of the biochar lignocellulose material to low molecular weight fractions [ 26 ]. As the biochar concentration increases, η* decreases more gradually till approaching a quasi-Newtonian η* plateau within the low–mid frequency range for both PBSA15 and PBSA20 composites.…”
Section: Resultsmentioning
confidence: 99%
“…The authors demonstrated the enhanced mechanical properties of wood-polypropylene matrices by the addition of 24 wt.% BC filler [ 23 ]. Since then, BC fillers have been widely studied in different thermoplastic formulations, such as polyolefins, ultra-high-density polyethene, polyamide, polyesters (PLA, PBT, PTT, and PET), and polycarbonates [ 24 , 25 , 26 , 27 ]. Due to their numerous applications, BC-epoxy resins are one of the most researched thermosetting matrices.…”
Section: Introductionmentioning
confidence: 99%
“…42,43 Bioderived carbon nanomaterials sculptured via pyrolysis have a high specific surface area (SSA), are thermally stable, and are porous in nature. 44–46 Biomass-derived carbon as a replacement for chemically synthesized carbon materials will not only contribute towards waste management but also provides the potential for large-scale production.…”
Section: Introductionmentioning
confidence: 99%